2015
DOI: 10.1002/2015ja021454
|View full text |Cite
|
Sign up to set email alerts
|

Field‐aligned currents in Saturn's northern nightside magnetosphere: Evidence for interhemispheric current flow associated with planetary period oscillations

Abstract: We investigate the magnetic perturbations associated with field‐aligned currents observed on 34 Cassini passes over the premidnight northern auroral region during 2008. These are found to be significantly modulated not only by the northern planetary‐period oscillation (PPO) system, similar to the southern currents by the southern PPO system found previously, but also by the southern PPO system as well, thus providing the first clear evidence of PPO‐related interhemispheric current flow. The principal field‐ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
284
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 73 publications
(324 citation statements)
references
References 55 publications
37
284
3
Order By: Relevance
“…6), in a multi-instrument study of Cassini data in the dusk to midnight sector, compatible with these results. They also found that the poleward boundary of the main upward field-aligned current region, presumed associated with the main auroral region, lay on average ∼ 1.8 • equatorward of this in the Northern Hemisphere, thus typically at ∼ 15.1 • in this LT sector, compatible with the results of Hunt et al (2015). Given a similar small equatorward displacement of the auroral oval from the open-closed boundary in the near-noon sector, we would thus expect its poleward boundary in the Northern Hemisphere to lie just equatorward ∼ 10 • on the basis of most of the results in Fig.…”
Section: Linear Approximation Paraboloid Model Parameterssupporting
confidence: 77%
See 1 more Smart Citation
“…6), in a multi-instrument study of Cassini data in the dusk to midnight sector, compatible with these results. They also found that the poleward boundary of the main upward field-aligned current region, presumed associated with the main auroral region, lay on average ∼ 1.8 • equatorward of this in the Northern Hemisphere, thus typically at ∼ 15.1 • in this LT sector, compatible with the results of Hunt et al (2015). Given a similar small equatorward displacement of the auroral oval from the open-closed boundary in the near-noon sector, we would thus expect its poleward boundary in the Northern Hemisphere to lie just equatorward ∼ 10 • on the basis of most of the results in Fig.…”
Section: Linear Approximation Paraboloid Model Parameterssupporting
confidence: 77%
“…We note that the model does not include a representation of the quasisteady internal field-aligned current system associated with subcorotation of the magnetospheric plasma (Hunt et al, 2014(Hunt et al, , 2015, which in general will cause a small deviation in LT of the field mapping between the equatorial plane and the ionosphere. Inclusion of related effects associated with the rotating "planetary period oscillation" (PPO) current system is also beyond the scope of the model.…”
Section: Saturn Paraboloid Modelmentioning
confidence: 99%
“…Hunt et al [2014] have reported PPO modulations of the southern hemisphere field-aligned current system. Further work by Hunt et al [2015] provided the first evidence of interhemispheric PPO-related field-aligned currents, as previously suggested by Southwood and Kivelson [2007]. Badman et al [2015] reported a solar wind compression impacting on Saturn's magnetosphere, describing an enhancement in the northern hemisphere field-aligned currents at the time of this solar wind compression.…”
Section: Discussionmentioning
confidence: 51%
“…Cowley et al (2004a) suggested that strong upward field-aligned currents associated with the auroral emissions are generated due to the azimuthal velocity shear between closed and open field lines. Closed field lines corotate with modest lag from rigid corotation, while on the open field lines corotation partially breaks dawn (with ∼ 30 % of rigid corotation; Stallard et al, 2004;Hunt et al, 2015), as they are dragged tailward by the solar wind. The strong upward field-aligned currents flowing at the boundary between the two different types of field lines are carried by downwardaccelerated magnetospheric electrons, which excite auroral emissions at ionospheric height in the auroral oval.…”
Section: Comparison Of Open and Partially Closed Saturn Magnetospherimentioning
confidence: 99%
“…In this paper the term "polar cap" is taken to be the area bounded by the auroral oval. Since the strong upward currents associated with the auroral oval are located on closed field lines just equatorward of the open-closed boundary (Jinks et al, 2014;Hunt et al, 2015), this polar cap region will consist almost wholly of open field lines. However, strong field-aligned currents at the boundary between topologically different field regions could arise not only in the case of an open magnetosphere.…”
Section: Comparison Of Open and Partially Closed Saturn Magnetospherimentioning
confidence: 99%